Human factors in online communities and social computing - Zaphiris, Panayiotis; Ozok, Ant (My University, 2012)
This chapter contains sections titled: •Introduction •Definition of Online Communities •Brief History of Communities in Society and their Function •Today's Online Communities and their Functions •Types of Computer-Mediated Communication and Online Communities •Analyzing Online Communities: Frameworks and Methodologies •Case Studies •Future Issues in Online Community Design •References
Keywords: Analysis; Communities